Peran Pemerintah Desa Dalam Perubahan Pariwisata Osing Di Desa Kemiren Kecamatan Glagah Kabupaten Banyuwangi - Anastasia Murdyastuti; Nur Aini Mayasiana (Journal of Tourism and Creativity, 2020)
Abstract Banyuwangi Regency is actively developing tourism potential, one of which is osing culture because it is unique and exciting as part of osing community life which is very obedient and obedient to cultural values. Still, the osing community is dynamic so that the existence of osing culture which was only as a traditional ceremonial tradition, is now packaged into more interesting material that can be a spectacle that can be sold. The change is inseparable from the role of the village government to invite the public and the private sector to jump into more advanced conditions and even become a leading tourism object in Banyuwangi Regency. The research method used is qualitative, and data collection techniques by observation, documentation, and interviews — analysis of data with interactive models through data collection data presentation data reduction and concluding. The results showed that the role of the government in making changes was quite good as seen from changes in tourist attractions and attractions, amenities and accommodation, accessibility, and tourism image osing already adequate, complete and good condition, because of the similarity in seeing the same future in advancing its village, trusting and making changes with specific actions between the private government and the community, although there are still limited funds and differences in interests, the government provides consistent support and basis so as to demonstrate a mutually supporting synergy. Keyword: Role, village government, change, and tourism osin